Optimización de tiempos y métodos de trabajo en los procesos de fabricación en el área de chocolates de la empresa “Confiteca S.A.” para el incremento de la productividad. - León Valarezo, Hugo Gabriel (2021)
The purpose of this research study is to optimize work times and methods in the chocolate area of the company "Confiteca S.A." for increased productivity. In the investigation, the productive efficiency of the current labor force was analyzed, through the method of direct observation and taking of chronometric times, to later propose a proposal for optimization of times. The proposed study is presented as an investigative project, in which a field modality, applying techniques such as observation, interviews, timing, to evaluate the production process of the chocolate area. The results obtained allowed to identify the operational problems for each stage of the process as well as the low productivity due to the low efficiency and unproductive times in the workforce in which a standard time limit was not established in the manufacturing processes of products based on of chocolate in the company Confiteca SA For the collection of information, the work study method was analyzed, where analyzed the factors in the production process, giving priority to taking the current times of the activities, carried out by regression timing to zero with which the times of each process were established, obtaining a current total for the manufacture of dark chocolate of 2 days 7 hours and 42 minutes, for the manufacture of white chocolate of 2 days 7 hours and 32 minutes. For the reduction of unproductive times, a proposal for the standardization of times in the processes of crushing, torrefaction, mixing grinding, refining, conching, tempering, molding and packaging, with this it is intended to increase the efficiency of the workers identifying times out of range. Activities were also combined through the man-machine diagram, which allowed reducing unproductive times that did not add any value to the processes. It is concluded that in the chocolate area it was possible to increase productivity by 188.87 bales made of dark chocolate, and 260.84 bales of white chocolate made in a month of work, increasing efficiency by 19.99% and 14.03% respectively. This increase is due to the fact that times are optimized and there is a range of times established for each activity of the manufacturing processes of dark and white chocolate company Confiteca SA